2018
DOI: 10.3390/mi9070315
|View full text |Cite
|
Sign up to set email alerts
|

Design of Substrate Stretchability Using Origami-Like Folding Deformation for Flexible Thermoelectric Generator

Abstract: A stretchable thermoelectric (TE) generator was developed by using rigid BiTe-based TE elements and a non-stretchable substrate with origami-like folding deformation. Our stretchable TE generator contains flat sections, on which the rigid TE elements are arranged, and folded sections, which produce and guarantee the stretchability of a device. First, a simple stretchable device with a single pair of p-type and n-type BiTe-based TE elements was designed and fabricated. The TE elements were sandwiched between tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…To endow the TEGs of rigid cuboids with a certain stretchability level, Fukuie et al chose an origami-like PI substrate and assembled the TE cubes on it, thereby achieving 20% stretching deformation. [17] Lee et al proposed another method to soften the TEGs by using silver nanowires-based stretchable interconnects to connect paralleled cuboids to substitute traditional rigid copper electrodes, while the intermediate regions between cuboids were infiltrated with polydimethylsiloxane (PDMS) to hold the cuboids. [18] However, there exist detaching issues between soft PDMS and the rigid TE cuboids in a large bending or stretching situation.…”
Section: Introductionmentioning
confidence: 99%
“…To endow the TEGs of rigid cuboids with a certain stretchability level, Fukuie et al chose an origami-like PI substrate and assembled the TE cubes on it, thereby achieving 20% stretching deformation. [17] Lee et al proposed another method to soften the TEGs by using silver nanowires-based stretchable interconnects to connect paralleled cuboids to substitute traditional rigid copper electrodes, while the intermediate regions between cuboids were infiltrated with polydimethylsiloxane (PDMS) to hold the cuboids. [18] However, there exist detaching issues between soft PDMS and the rigid TE cuboids in a large bending or stretching situation.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the distribution of many sensors in various places in the environment has been proposed, and TEGs represent a potential power source for those sensors [3][4][5][6]. For example, there have been reports of bendable TEGs [7][8][9][10][11][12][13][14][15] and stretchable TEGs [16,17] for IoT devices or wearable devices that attach to curved heat sources (such as piping, car bodies, and the human body). In particular, a stretchable TEG is needed so that it can be attached with low thermal contact resistance to curved heat sources and harvest energy from them [16].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a stretchable TEG integrated with a fin for heat radiation has been necessitated. In previous studies, although the production of stretchable TEGs that used a folded substrate was reported, the folded substrate was not considered to be a heat radiation fin [17]. Therefore, we decided to develop a stretchable TEG with a high heat radiation performance that uses a folded substrate as a heat radiation fin.…”
Section: Introductionmentioning
confidence: 99%
“…Many recent studies have focused on the development of thermoelectric generators [1,2,3,4,5,6,7,8]. Thermoelectric generators are used to convert waste heat into electrical power, which is a green energy.…”
Section: Introductionmentioning
confidence: 99%